Kinerja Penerapan SIAK Dalam Meningkatkan Efisiensi Kinerja Pegawai Di Dinas Kependudukan Pencatatan Sipil Mamuju - Kato, Enjelina; Prisilia, Dela; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
Digital transformation in the public sector has encouraged various government agencies to begin utilizing information systems as a means of improving efficiency and service quality. One manifestation of this effort is the implementation of the Population Administration Information System (SIAK) at the Population and Civil Registration Office. This study aims to assess the performance of SIAK implementation in supporting increased employee work efficiency at the Population and Civil Registration Office of Mamuju Regency. The approach used was quantitative with descriptive methods. Data were obtained through observation, distribution of questionnaires to employees using SIAK, and documentation studies. The results show that the use of SIAK has a positive impact on employee performance efficiency, particularly in terms of speed of service completion, population data accuracy, and smooth work processes. However, the implementation of this system still faces several obstacles, particularly related to network quality and differences in technical capabilities among employees. Therefore, efforts to improve infrastructure and strengthen human resource competencies are needed continuously to optimize SIAK utilization.